A System Model Design to Match Fingerprints by Extracting Minutiae - Barman, Bandana; Paul, Ria (Indian Science Cruiser, 2016)
In the modern technologies the fingerprints are one of the most advanced biometric technologies and these are used as the proofs of a person’s evidence. In a fingerprint, the varieties of categories of minutiae are present. The most popular categories of minutiae are used in the fingerprint verification system. In this paper, a indigenous design model is proposed for fingerprint analysis by extracting minutiae of image. Correlation coefficient between the two fingerprint images is calculated after doing the preprocessing on input image until to get suitable minutiae. Additionally, the two important categories of minutiae and the bifurcation are used in this paper.